Correlation analysis of CD8+ cell overexpression and prognosis of hemorrhagic fever with renal syndrome—a case-control study - Wang, Min; Zhou, Yong; Wang, Ying; Du, Yanqiang; Guo, Zhangyan; Ma, Le; Zhang, Hua; Wang, Yi (Frontiers in Pediatrics, 2023)
Abstract Background: Hemorrhagic fever with Renal Syndrome (HFRS) is an infectious disease caused by Hantavirus with fever, hemorrhage and acute kidney injury (AKI) as clinical characteristics. The research on the etiology and pathogenesis of diseases has become a focus of attention. However, there are few related medical studies in children with HFRS. The prognosis of the children with HFRS remains to be explored. Objectives: We explored risk factors in children with HFRS and summarize sensitive indicators that are conducive to the prognosis of the disease. Methods: We designed a case-control study and recruited 182 HFRS pediatric patients(2014.01-2022.08). They were divided into two groups according to the severity of disease, including the control group(158 cases with mild and moderate subgroup)and the observation group (24 cases with severe and critical subgroup). Risk factors influencing prognosis were analyzed by binary logistic regression. The cutoff value, sensitivity and specificity of the risk factors prediction were calculated by receiver operating characteristic (ROC) and Yoden index. Results: Lymphocyte subsets characteristics analysis showed that in observation group the indexes were decreased in lymphocyte, T lymphocytes (CD3)+, helper/inducible T lymphocytes (CD4+)/ inhibition/cytotoxic T cells (CD8+), B lymphocytes (CD19+); and the elevated index was CD8+, the difference were all significant between two groups. (P < 0.05). With death as the primary outcome, it was found that the serum CD8+ (odds ratio [OR] 2.91, 95% confidence interval[CI] 1.65, 4.00; P < 0.01) was risk factor and significantly associated with mortality. The cutoff value of the serum CD8+ was 845×106/L, the sensitivity and specificity were 78.5%, 85.4%. With complications as the secondary outcomes, the serum CD8+ (OR 2.69, 95% CI 1.15, 4.88; P < 0.01) was found to be risk factors. The cutoff of the serum CD8+ was 690×106/L, the sensitivity and specificity were 69.3%, 75.1% respectively. Conclusion: CD8+ may be significantly correlated with the severity and prognosis of HFRS in children.